Desiminasi Sistem Pembangkit Tenaga Surya untuk Guru dan Siswa di Kabupaten Bandung - Bandiyah Sri Aprillia; Mohamad Ramdhani; Irwan Purnama (Warta LPM, 2023)
Utilization of solar energy requires an active role from the community by providing information related to solar energy and the potential that can be obtainedIt is necessary to provide guidance to the community by providing basic knowledge about the conversion of solar energy into electricity. Followed by doing practice in proving the basic knowledge given in the form of simple practice. So that the public can understand information related to solar energy as a whole, both basic knowledge, conversion techniques, and installation techniques. The purpose of this community service is to provide training on solar power plant installations as a learning medium in the use of renewable energy in the form of solar energy. The training targets are MA teachers and students as the next generation who in the future will face greater challenges related to energy utilization. MA students are currently required to be more creative and innovative in utilizing all the potential of nature, especially the use of alternative technologies, one of which is solar energy. The Pangalengan area is also a challenge in itself in the use of electricity technology for the need for support by using solar energy for electricity use. In the community service program, an On-Grid 260 Wp solar power plant system has been installed which aims as a learning medium and helps reduce monthly school costs by integrating solar panels for the electrification of the Natural Sciences Laboratory (IPA).